الزواج العرفي في الفقه الإسلامي وقانون الأسرة الجزائري - فرحات هاجر (جامعة المسيلة, 2022)
هدفت هذه الدراسة إلى معرفة منهج الزواج العرفي وحكمة في الفقه الإسلامي، ودراسة مفهومة وأهميته، من قبل أهل العلم. وتكمن إشكالية البحث: في اختلاف أهل العلم في تعريفه وڅکمه، وتأتي أهمية الموضوع: إنه يبين فيه حفظ النسل وهو مقصد من مقاصد التشريع، وحفظ الحياة الاجتماعية، والقيم للمجتمع، وقد سلك الباحث في دراسته: المنهج الاستقرائي في جمع الآراء والأقوال، ثم المنهج التحليلي؛ وذلك باستنباط وتحليل قول العلماء وبيان حالهم وحكمهم، وتتلخص أهم نتائج البحث: إن عقد النكاح العرفي بين رجل وامرأة، من غير ولي ولا شهود، باطل باتفاق أهل العلم، وإن كان عقد النكاح العرفي من غير شهود، فهو باطل أيضا عند الحنفية والشافعية والحنابلة. أما المالكية فلم يشترطوا حضور الشهود في العقد، لكن اشترطوا إعلان النكاح وظهوره، وأوجبوا الشهادة قبل الدخول، وإن كان عقد النكاح العرفي من غير ولي. فهو باطل عند الجمهور. الكلمات المفتاحية : الزواج العرفي؛ نکاح؛ عقد؛ الفقه الإسلامي. Abstract: This research aims to know the method of common-law marriage and its rule in Islamic fiqh, and to study its concept, importance and judgment, by Ulams. The problem of the subject lies in the difference between Ulam in its definition and ruling. The importance of the topic is that it shows the preservation of the offspring and it is one of the purposes of the legislation, and it preserves social life and community values. ; The most important results of this research paper are summarized if the customary marriage contract is between a man and a woman, without a guardian or witnesses, then it is invalid according to the agreement of the Ulam, and if the customary marriage contract is without witnesses, then it is also invalid according to the Hanafis. The Shafi'is and Hanbalis, and as for the Malikis, did not stipulate the presence of witnesses in the contract, but required the declaration and appearance of the marriage, but rather required testimony before entering, and if the customary marriage contract was without a guardian, then it is also invalid for the majority. Keywords: Al-Arefi, marriage, contract, Islamic Figh.
Keywords: : الزواج العرفي؛ نکاح؛ عقد؛ الفقه الإسلامي